Measurement of high time-bandwidth pulses on a chip with SPIDER - Pasquazi, Alessia; Peccianti, Marco; Morandotti, Roberto; Azana, Jose; Moss, David J. (Photonics Letters of Poland, 2012)
We develop a method capable of characterizing both the amplitude and phase of ultrafast optical pulses with the aid of a synchronized incoherently-related clock pulse based on a novel variation of SPIDER. It exploits degenerate four-wave-mixing and its design is amenable for full ?on chip? signal characterization. By implementing our method in a CMOS compatible waveguide, we measure pulses with < 100mW peak power, a frequency bandwidth > 1THz, and up to 100ps pulsewidths. Our novel reconstruction algorithm that we call Fresnel-Limited Extraction Procedure (FLEA), yields a time-bandwidth product (TBP)>100. Full Text: PDF References R. Trebino, "Frequency Resolved Optical Gating: the Measurement of Ultrashort Optical Pulses", (Kluwer Academic, 2002)[CrossRef] I. A. Walmsley and C. Dorrer, "Characterization of ultrashort electromagnetic pulses", Adv. Opt. Photon. 1, 308-437 (2009)[CrossRef] Nature Photonics Workshop on the future of optical communication,Tokyo, Oct. 2007. M. A. Foster et al.,"Silicon-chip-based ultrafast optical oscilloscope", Nature 456, 81-84 (2008)[CrossRef] E. K. Tien, X. Z. Sang, F. Qing, Q. Song, and O. Boyraz., "Ultrafast pulse characterization using cross phase modulation in silicon", Appl. Phys. Lett. 95, 051101 (2009)[CrossRef] A. Pasquazi et al.,"Sub-picosecond phase-sensitive optical pulse characterization on a chip", [CrossRef] C. Iaconis and I.A. Walmsley,"Spectral phase interferometry for direct electric-field reconstruction of ultrashort optical pulses", Opt. Lett., 23, 792-794 (1998)[CrossRef] L. Gallmann et al.,"Characterization of sub-6-fs optical pulses with spectral phase interferometry for direct electric-field reconstruction", Opt. Lett., 24, 1314-1316 (1999)[CrossRef] C. Dorrer et al.,"Single-shot real-time characterization of chirped-pulse amplification systems by spectral phase interferometry for direct electric-field reconstruction", Opt. Lett., 24, 1644-1646 (1999)[CrossRef] D. Keusters et al.,"Relative-phase ambiguities in measurements of ultrashort pulses with well-separated multiple frequency components", J. Opt. Soc. Am. B, 20, 2226-2237 (2003)[CrossRef] M. Hirasawa et al.,"Sensitivity improvement of spectral phase interferometry for direct electric-field reconstruction for the characterization of low-intensity femtosecond pulses", Appl. Phys. B, 74, S225-S229 (2002)[CrossRef] J. Wemans, G. Figueira, N. Lopes and L. Cardoso,"Self-referencing spectral phase interferometry for direct electric-field reconstruction with chirped pulses", Opt. Lett., 31, 2217-2219 (2006)Self-referencing spectral phase interferometry for direct electric-field reconstruction with chirped pulses[CrossRef] M. Peccianti et al.,"Subpicosecond optical pulse compression via an integrated nonlinear chirper", Opt. Express, 18, 7625-7633 (2010)[CrossRef] A. Pasquazi et al.,"All-optical wavelength conversion in an integrated ring resonator", Opt. Express 18, 3858-3863 (2010)[CrossRef]